Periodontally accelerated osteogenic orthodontics: An interdisciplinary approach for faster orthodontic therapy - Srikanth Adusumilli (Journal of Pharmacy and Bioallied Sciences, 2014)
Periodontally accelerated osteogenic orthodontics is a relatively new procedure designed to minimize the time taken for orthodontic treatment. The orthodontist avails of the aid of a periodontist to perform decortication of the bone and places bone graft for rapid orthodontic correction of malocclusion. A PubMed search was carried out to identify papers describing the procedure, and the data were organized in the current format.